Protein hydrolysates and phenolic compounds from fermented black beans inhibit markers related to obesity and type‐2 diabetes. Issue 1 (4th October 2020) - Flores‐Medellín, Sergio A.; Camacho‐Ruiz, Rosa M.; Guízar‐González, Cecilia; Rivera‐Leon, Edgar A.; Llamas‐Covarrubias, Iris M.; Mojica, Luis
Abstract: Obesity and type 2 diabetes mellitus (T2DM) represent an epidemic and public health problem. Bioactive compounds from foods could be used as adjuvants in the prevention of these diseases. Processes such as solid‐state fermentation (SSF) have demonstrated to improve the release of bioactive compounds from food matrix. This project aimed to evaluate the effect of fermented black bean ( Phaseolus vulgaris L.) phenolic compounds and protein hydrolysates on markers associated with obesity and T2DM. Twenty‐eight peptide sequences and 12 phenolic compounds were identified on black bean samples. From in silico assays, sequenced peptides showed theoretical binding energies up to −9.8 kcal/mol and phenolic compounds up to −10.1 kcal/mol for monoacylglycerol lipase. Protein hydrolysates from SSF 96 h (12 peptides) showed the potential to inhibit α‐amylase with inhibitory concentration 50 (IC50 ) 0.57 mg protein/ml and 5.55 mg protein/ml for α‐glucosidase. Phenolic compounds from SSF 48 h blocked α‐glucosidase IC50 0.353 mg GAE/ml. The antioxidant capacity was maintained in phenolic compounds after fermentation for 48 h and improved in the protein hydrolysates. Raw bean protein hydrolysates (0.1 mg protein/ml) presented the potential to inhibit lipid accumulation in 3T3‐L1 cell line (27.9%). SSF is a processing method for generating functional ingredients rich in bioactive compounds capable of acting on biological markers related to the treatment or prevention of obesity and T2DM.